Regulatory effects of Xihu Longjing tea on the intestinal flora of mice fed with high-fat and high-fructose diet - HU Liquan; TU Linyue; ZHAO Yueling; XIE Hengtong; XU An’an; XU Ping; ZHOU Jihong; WANG Yuefei (浙江大学学报. 农业与生命科学版)
An increasing number of studies have shown that the intestinal flora and microbial ecology mediated by the intestinal flora play key roles in metabolic disorders associated with high-fat and high-fructose diet. In this study, we investigated the effects of Xihu Longjing tea on the intestinal flora of mice fed with a conventional diet, followed by the construction of a mouse model with a high-fat and high-fructose diet to investigate the effects of Xihu Longjing on the prevention of lipid accumulation, intestinal barrier function impairment and intestinal microecological disorders in mice fed with high-fat and high-fructose diet. The results showed that Xihu Longjing tea soup inhibited the body mass gain and lipid accumulation in mice fed with a high-fat and high-fructose diet and effectively relieved metabolic disorders. When investigating the protective effects of Xihu Longjing on intestinal homeostasis in mice fed with a high-fat and high-fructose diet, it was found that Xihu Longjing tea soup treatment inhibited the expression of hypoxia inducible factor-1α (HIF-1α) and its target genes enolase-1 (ENO1)andlactate dehydrogenase A (LDHA) in the intestinal epithelial cells of mice. In addition, Xihu Longjing tea soup intervention reduced the abundance of intestinal bacteria of Firmicutes/Bacteroidota ratio and enriched the abundance of probiotic bacteria such as norank_f_Muribaculaceaein mice, and then the high-fat and high-fructose diet with low concentration of Xihu Longjing treatment enriched Lachnospiraceae bacteria and the high-fat and high-fructose diet with high concentration of Xihu Longjing treatment increased the relative abundance of Oscillospirales bacteria. The results provide a theoretical basis for Longjing tea to regulate fat accumulation by improving intestinal flora disorders, and provide theoretical support for the ability of tea consumption to improve intestinal health and play a role in fat reduction and body mass loss.